Gender difference in the prevalence and socio-demographic correlates of mobility disability among older adults in Nigeria - Balogun, Saliu Adejumobi (Eur J Ageing, 2016)
The aim of the current study is to examine gender differences in mobility disability among older people in Nigeria, and to explore factors associated with gender differences in mobility disability in later life. Data were used from the first (2010–2011) wave of the Nigeria General Household Survey-Panel, which included 3586 respondents aged 50 years and above. Mobility disability was assessed as self-reported difficulty in walking 100 m, walking 1 km, walking uphill, running, bending or stooping, and climbing stairs. Regression analyses were used to estimate the extent to which socio-demographic conditions contribute to gender differences in mobility disability. We observed a higher prevalence of mobility disability among women compared to men (20.1 vs. 12.5 %, P < 0.001). The prevalence ratios (PR) of mobility disability for women versus men was 1.61 (95 % CI 1.38–1.88, P < 0.001); after adjusting for age, marital status, place of residence, self-reported health status and cognitive difficulties, the PR was 1.55 (95 % CI 1.30–1.85, P < 0.001). In the fully adjusted model, mobility disability still remained significantly higher among women (PR 1.60, 95 % CI 1.32–1.93, P < 0.001). The marginal effects of socio-demographic and health factors were stronger for women than for men. Socio-demographic and health variables considered in this study explained between 19.3 % (men) and 22.3 % (women) of variance in mobility disability suggesting that additional factors beyond those considered in this study warrant further investigation, so that differences in mobility disability between older men and women in Nigeria can be fully understood. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10433-016-0386-z) contains supplementary material, which is available to authorized users.